Importance of the Caspian Countries for the European Union Energy Security - Ibrayeva, Aigerim; Sannikov, Dmitriy V.; Kadyrov, Marsel A.; Zapevalov, Vladimir N.; Hasanov, Elnur L.; Zuev, Vladimir N. (International Journal of Energy Economics and Policy, 2018)
When there is a lack of energy resources in the EU and it has to look for suppliers from other countries, Russia provides the world with most of the oil and gas. Diversification of energy resources is one of the objectives for the EU. The majority of international participants are interested in discovering the potential of the sea. However, the development of the region’s resources still faces many obstacles, such as lack of export pipelines, difficulties due to security of supply considerations, transit complications, political and legal considerations and market uncertainties. This study focuses on the countries of the former Soviet Union such as Uzbekistan, Kazakhstan and Turkmenistan in Central Asia, and Azerbaijan in Transcaucasia. One of the six priority areas of the EU in the energy infrastructure of - the Southern Energy Corridor (SEC), the purpose of which is to link the Caspian basin and potentially Middle Eastern gas to Europe. In the article, we analyzed the potential of the Caspian basin in terms of energy and its impact on the energy security of the European Union. Keywords: Caspian Sea, Central Asia, European Union, Southern Corridor, Pipeline, Energy Security JEL Classifications: F52, H55, H56.